Reward system and performance within Malaysian manufacturing companies - Ong, Tze San; Teh, Boon Heng (IDOSI Publications, 2012)
This study examines the relationship between the reward system and organization’s financial performance. Data is collected through a questionnaire survey covering 105 manufacturing companies in Malaysia. Data gathered is analyzed quantitatively such as linear regression analysis is adopted in order to investigate the interrelationship between research variables. Results and findings of this study include: (1) most of the manufacturing firms provide both monetary and non-monetary rewards; (2) adoption of reward system is not influenced by age and size of the company; (3) negative relationship exists between extrinsic rewards and financial performance of organizations and (4) intrinsic rewards are positively related to financial performance of organizations. This study has provided important information into the implementation of reward system on organization’s performance.